2012
DOI: 10.1371/journal.pone.0029775
|View full text |Cite
|
Sign up to set email alerts
|

Health Related Quality of Life among Patients with Tuberculosis and HIV in Thailand

Abstract: IntroductionHealth utilities of tuberculosis (TB) patients may be diminished by side effects from medication, prolonged treatment duration, physical effects of the disease itself, and social stigma attached to the disease.MethodsWe collected health utility data from Thai patients who were on TB treatment or had been successfully treated for TB for the purpose of economic modeling. Structured questionnaire and EuroQol (EQ-5D) and EuroQol visual analog scale (EQ-VAS) instruments were used as data collection tool… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
54
3
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(68 citation statements)
references
References 35 publications
8
54
3
3
Order By: Relevance
“…Furthermore, this study used the SF36v2 tool and designed questionnaire which were particularly quantitative. This tool was not validated in the study population and although this is likely to influence the outcome, the findings from this study were still consistent with studies in other population [1, 11]. Qualitative methods like in-depth interviews and focus group discussions would have provided deeper explanations behind the observed HRQoL scores.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…Furthermore, this study used the SF36v2 tool and designed questionnaire which were particularly quantitative. This tool was not validated in the study population and although this is likely to influence the outcome, the findings from this study were still consistent with studies in other population [1, 11]. Qualitative methods like in-depth interviews and focus group discussions would have provided deeper explanations behind the observed HRQoL scores.…”
Section: Discussionsupporting
confidence: 61%
“…However, TB therapy presents some demerits that impact on patient’s health-related quality of life (HRQoL). This may be due to drug toxicity, adverse drug reactions [22], social stigma [10, 11] or the anxiety and a feeling of helplessness stimulated by the disease and its treatment processes [15]. These effects determine the way patients perceive their total health and wellbeing, which is defined as HRQoL [21].…”
Section: Introductionmentioning
confidence: 99%
“…This is supported by recent work showing a similar loss in quality of life measured by EQ-5D in those with active drug-sensitive TB with or without HIV coinfection [29]. Our analysis has been from a clinical perspective and has only used the potential costs and health status in those subjects tested.…”
Section: Principal Findingsmentioning
confidence: 53%
“…Brazilian researchers [5,8,10,12,13,14] found that better levels of quality of life of HIV patients were related to better financial conditions, as with the results of the present study. Other study [15], also showed better QoL indicators associated with increased income.…”
Section: Discussionmentioning
confidence: 67%
“…This is fundamental to continuity of treatment and client follow-up. Corroborating this, a more holistic approach, which was not confined to coinfection treatment, was beneficial to the QoL [15].…”
Section: Discussionmentioning
confidence: 96%